1997
DOI: 10.1093/jnci/89.23.1789
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Continuous-Infusion L-S,R-Buthionine Sulfoximine With Intravenous Melphalan

Abstract: Continuous-infusion BSO is relatively nontoxic and results in depletion of tumor glutathione.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 22 publications
6
111
0
2
Order By: Relevance
“…BSO has already been clinically used as a potential sensitizer of L-PAM, an alkylating anticancer agent. 7,8 In our examination, the IC 50 values of L-PAM on PC-3 and DU145 cells were 105.0718.0 and 9.972.3 mM, respectively. Addition of 10 mM BSO decreased these IC 50 values of L-PAM by 1.4-and 1.6-fold in PC-3 and DU145 cells, respectively.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…BSO has already been clinically used as a potential sensitizer of L-PAM, an alkylating anticancer agent. 7,8 In our examination, the IC 50 values of L-PAM on PC-3 and DU145 cells were 105.0718.0 and 9.972.3 mM, respectively. Addition of 10 mM BSO decreased these IC 50 values of L-PAM by 1.4-and 1.6-fold in PC-3 and DU145 cells, respectively.…”
Section: Resultsmentioning
confidence: 57%
“…7 Subsequent clinical trials with L-PAM plus BSO, however, did not show therapeutic effects on advanced solid tumors. 8 Our in vitro growth inhibition assays provide experimental evidence for this failure in clinical trials. In prostate cancer cell lines treated with 10 mM BSO, the degree of sensitization was only a 1.4-1.6-fold decrease in IC 50 values of L-PAM.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Since then, three Phase I clinical trials using BSO in combination with melphalan have been reported [66][67][68]. One Phase I trial showed significant responses to the BSO/melphalan combination [67], and two clinical trials using the same combination are currently being conducted, one at the Phase I level (New Approaches to Neuroblastoma Therapy Consortium, USA.…”
Section: Bso: Animal Studies and Clinical Trialsmentioning
confidence: 99%